The Students Perception toward the Teachers Teaching Method at the Tenth and Eleventh Grades of Pesantren Modern Datok Sulaiman Palopo - Wahibah Wahibah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2015)
The objective of this research as to find out the students perception toward the teachers teaching method at the tenth and eleventh grades of Pesantren Modern Datok Sulaiman Palopo.